Revival of the Russian chemical industry during the Soviet period (1917–1927). Part 2 - K. S. Guzev (Разработка и регистрация лекарственных средств)
The second part of the article contains materials on the further structuring of the domestic industry and the formation of trusts, the development of a classification of chemical industries and the organization of the Scientific and Technological Department of the Supreme Economic Council (NTO). The special attitude of the country's leadership towards the old personnel and organizations that ensure the operation of enterprises in this industry, as well as the government's concern for the education of young domestic chemists grown in Russia, is shown. A special place is occupied by the work on organizing the involvement of former owners of plants and factories in the restoration of their enterprises. On the initiative of VN Ipatiev, work began on the organization of a concession commission under the State Planning Committee. The second part contains materials on the further structuring of the domestic industry and the formation of trusts, the development of a classification of chemical industries and the organization of the Scientific and Technological Department of the Supreme Economic Council (NTO). The special attitude of the country's leadership towards the old personnel and organizations that ensure the operation of enterprises in this industry, as well as the government's concern for the education of young domestic chemists grown in Russia, is shown. A special place is occupied by the work on organizing the involvement of former owners of plants and factories in the restoration of their enterprises. On the initiative of VN Ipatiev, work began on the organization of a concession commission under the State Planning Committee.